Set Size and Donation Behavior - Lindkvist, Amanda M.; Luke, Timothy J. (Frontiers in Psychology, 2022)
Choice overload is the phenomenon that increasing the number of options in an assortment makes choosing between options more difficult, sometimes leading to avoidance of making a choice. In this pre-registered online experiment (N = 501), choice overload was tested in a charitable behavior context where participants faced a monetary donation choice. Charity organization assortment size was varied between groups, ranging between 2-80 options. The results indicate that there were no meaningful differences in donation likelihood between the 16 organization assortment sizes, neither for individuals with high preference certainty nor for individuals with uncertain preferences among charitable causes. Having more charitable organizations to choose from did not affect donation behavior.